Tax Planning PT Mayora Indah Tbk: Harmonizing Compliance And Tax Optimization - Khoirunnisa, Novita; Prawira, Ida Farida Adi; Kustiawan, Memen (Universitas Muhammadiyah Makassar, 2025)
Tax planning is an important element in financial management that aims to minimize the tax burden that must be paid by the company. In this case, tax planning does not only focus on efforts to reduce the tax burden, but also is a strategy designed to ensure compliance with applicable tax regulations. This study aims to analyze the tax planning strategy implemented at PT Mayora Indah Tbk to align compliance with tax regulations with the optimization of the company's tax burden. This research uses a descriptive qualitative method by analyzing secondary data in the form of the Annual Report of PT Mayora Indah Tbk in 2022 and 2023 published on the Indonesia Stock Exchange. The results showed that the implementation of tax planning at PT Mayora Indah Tbk by converting costs that cannot be deducted from gross income (non deductible expense) into costs that can be deducted from gross income (deductible expense) is effective in reducing the company's tax burden so that the profit earned by the company remains optimal. Through tax planning, the company obtained tax savings for 2023 amounted Rp11,668,828,189 and 2022 amounted Rp12,523,559,687. Thus, PT Mayora Indah Tbk can optimize cost efficiency while still complying with applicable tax regulations. The results of this study are expected to be a reference for tax practitioners in designing effective tax planning policies.